Foreign aid and foreign direct investment, corruption, and economic growth in Sub-Saharan African countries - Mohamed, Masoud Rashid (2014)
For over forty years, foreign aid has been one of the key development instruments for Sub-Saharan African (SSA) countries, specifically, and the African region as a whole. Foreign aid is largely channeled to assist the growth of the recipient countries by supplementing savings and foreign exchange constraints of the recipient countries. However, despite the huge flow of aid to SSA countries, economic growth is still low. This makes the region underdeveloped with high poverty rates. Besides foreign aid, SSA countries also experience a substantial increase in the flows of foreign direct investment (FDI), although the share is still small compared to the flows of FDI to other developing countries as a whole. Despite having more FDI now compared to previous decades, the region still experiences low economic growth. Another important issue in this respect is that the literature reveals that foreign aid and FDI cannot promote growth if they are associated with a higher level of corruption as corruption itself discourages growth. Against this background, this study intends to a) analyze the long run relationship between foreign aid, FDI and economic growth in Sub-Saharan African countries; (b) explore the empirical nexus between foreign aid and FDI flows in SSA countries; and (c) investigate the impact of foreign aid flows on the level of corruption in SSA countries. Two methodologies were used to achieve the stated objectives. For the first and second objectives, the Generalized Method of Moments (GMM) approach was used, while for the third objective, a Quantile Regression approach was applied. The analyzed data covered the period of 1996 to 2010 for the first objective (with 41 sample countries); 1990 to 2010 for the second objective (45 countries); and 2000 to 2010 for the third objective (42 countries). The findings reveal that while foreign aid has a negative effect on growth, the impact of FDI is positive but statistically insignificant. Aid from different bilateral donors was found to have a different impact on growth. The results further indicate that all three categories of aid (total, bilateral, and multilateral) have a direct positive effect on the flow of FDI. Moreover, the findings indicate that poor institutional quality is associated with the low inflow of FDI into SSA countries. Concerning the link between foreign aid and corruption, the results show that aid has the tendency of increasing the corruption levels of SSA countries. The results further reveal that aid from different bilateral sources has a different impact on corruption. That is, aid from some bilateral donors such as France and US reduce corruption while aid from some other bilateral donors (UK, Canada, and Germany) increases corruption. Based on the findings, the study suggests that the allocation of aid should be targeted towards the improvement of institutional quality in order to generate the desired outcome of high economic growth. Moreover, it is highly crucial to ensure that the aid fund is allocated to the most productive sectors so that a substantial improvement could be achieved in the economic growth and welfare of SSA countries. This could be achieved if the coordination between the various donors (bilateral and multilateral) is also improved. Since current allocation of aid seem to be associated with increase of corruption, the allocation policy should be revisited to ensure that aid improve the quality of institution and governance of recipient countries in order to reduce the level of corruption. This would eventually ensure more inflows of aid and FDI in the future and will result in a noticeable impact on the economic growth of SSA countries.